Comparison of the Efficacy of Danhong Injections at Different Time-points During the Perioperative Period of Acute Myocardial Infarction: A Systematic Review and Meta-analysis of Randomized Controlled Trials - He, Qing-Ying; Yu, Xin-Yu; Xiao, Zheng; Sun, Xin; Zhu, Wei-Feng; Yi, Xing-Qian; Chen, Qian; Zhang, Jia-Hui; Chen, Shu-Xian; Zhou, Xu; Nie, He-Yun; Shang, Hong-Cai; et al. (Frontiers in Pharmacology, 2021)
Objectives: Danhong injections (DHI) are widely used in the treatment of acute myocardial infarction (AMI). As there are no guidelines for the timing of DHI in the peri-percutaneous coronary intervention (PCI) period for AMI, we investigated the effects of DHI timing. Methods: We reviewed reports published before September 30, 2020 in PubMed, embase, the Cochrane Central Register of Controlled Trials, the Chinese BioMedical database, Chinese VIP database, Wanfang database, and Chinese National Knowledge Infrastructure database. Only randomized controlled trials of DHI with percutaneous coronary intervention for AMI were included. Methodological quality was assessed using the Cochrane evaluation manual 5.3.3 criteria. A meta-analysis was performed, and forest plots were drawn. Results: We included 23 studies which all revealed that patients in DHI groups had better efficacy than control groups. Subgroup analysis revealed that DHI administered intraoperatively and continued postoperatively was more effective in increasing left ventricular ejection fraction when compared to other time-points (p < 0.001). The pre- and intraoperative use of DHI could improve reflow more effectively than conventional treatment, while the effect was not significant in the postoperative intervention study (p = 0.654). The 16 postoperative interventions revealed that the effect of DHI at 14 days was better than that at 7 and 10 days for hs-CRP (p = 0.013), the 10-days treatment produced better results for CK-MB than for the other treatments (p < 0.001) and a dosage of 30 ml proved most effective for IL-6 (p < 0.001). Conclusion: DHI proved to be superior to conventional Western medicine in reducing the incidence of adverse cardiac events, promoting reperfusion, improving cardiac function, reducing inflammatory factors, and protecting the myocardium. DHI should be administered early in the perioperative period and continued postoperatively because of its ability to improve cardiac function. Furthermore, in the PCI postoperative, 30 ml is recommended to inhibit IL-6 levels, for patients with high hs-CRP, a course of 14 days is most effective, for patients with obvious abnormalities of CK-MB, a 10-days course of treatment is recommended. However, due to the limited number and quality of the original randomized controlled trials, our conclusions need large, multi-centre RCTs to validation.